2018
DOI: 10.1024/1422-4917/a000614
|View full text |Cite
|
Sign up to set email alerts
|

Schlaf und Kognition bei Kindern und Jugendlichen

Abstract: Sleep and cognition in children and adolescents Abstract. In this review, one of the most important functions of sleep was described: Its role in promoting cognitive processes in children and adolescents. Particularly, studies of older children and adolescents revealed that sleep interacts in a complex manner with cognitive performance. Moreover, it was shown that sleep supports long-term memory even in young children. This is true for many different long-term memory systems such as memory of factual informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 136 publications
0
4
0
Order By: Relevance
“…Sufficient duration and quality of sleep have been shown to be important for the development of memory, language, sustained attention, processing speed and executive functions 60–62 . Shorter sleep duration in the first 3 years in healthy children is also associated with hyperactivity and lower cognitive performance on neurodevelopmental tests at age 6, demonstrating that inadequate sleep in early life can produce long‐standing effects on neurocognitive function 63 .…”
Section: Sleep and Neurocognitive Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Sufficient duration and quality of sleep have been shown to be important for the development of memory, language, sustained attention, processing speed and executive functions 60–62 . Shorter sleep duration in the first 3 years in healthy children is also associated with hyperactivity and lower cognitive performance on neurodevelopmental tests at age 6, demonstrating that inadequate sleep in early life can produce long‐standing effects on neurocognitive function 63 .…”
Section: Sleep and Neurocognitive Developmentmentioning
confidence: 99%
“…Sufficient duration and quality of sleep have been shown to be important for the development of memory, language, sustained attention, processing speed and executive functions. [60][61][62] Shorter sleep duration in the first 3 years in healthy children is also associated with hyperactivity and lower cognitive performance on neurodevelopmental tests at age 6, demonstrating that inadequate sleep in early life can produce long-standing effects on neurocognitive function. 63 A study in preterm babies, evaluating whether sleepwake state organization was related to developmental milestones in the first year after birth revealed that the stability and duration of sleep may be predictive of mental performance at 24 and 52 weeks of age.…”
Section: S Leep and Neuro Cog Nitive De Velopmentmentioning
confidence: 99%
“…Sleep is a relevant factor for the healthy development of children and adolescents and, due to the regenerative processes associated with it, is central for health and well-being. Sufficient and undisturbed sleep is essential for cognitive functioning and performance [ 1–3 ] and is positively associated with academic performance in children and adolescents (for an overview, see [ 3–5 ]). Physical parameters, such as, for example, overweight/obesity and cardiovascular risk factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Information relating to the further social differentiation is not yet available for the KiGGS baseline study. International surveys support a social gradient for sleep problems, and children from socially disadvantaged families are also affected more strongly by the negative effects of a lack of sleep than children from socially advantaged families [ 3 , 25 ].…”
Section: Introductionmentioning
confidence: 99%